Using Communities of Practice to Enhance Diabetes Education - Catherine H. Monaghan (Adult Education Research Conference, 2015)
This session presents the results of a pilot study in Diabetes education using a model, SystemCHANGE™ within a Communities of Practice. Communities of Practice can be incorporated effectively in patient health education to produce sustainable behavioral changes to affect an individual’s ability to manage a chronic disease in a positive manner.
Keywords: community of practice; diabetes education; mixed methods research